INDONESIAN UNIVERSITY STUDENT'S EMOTIONAL EXPERIENCES OF LEARNING VOCABULARY THROUGH ENGLISH LEARNING ACCOUNTS ON INSTAGRAM - Iwan Gunawan; Yousef Bani Ahmad; Praditya Putri Utami (Eltin Journal : Journal of English Language Teaching in Indonesia, 2021)
Emotions are indicated as central heart in the term of vocabulary learning context. These are being students’ evaluation toward foreign language learning process that provide worthwhile and important information related to cognition, behaviour and even motivation. In this case, the investigation of emotions which personally experienced by university students has not existed in the forefront, still gets a little bit scientific attention, quite limited in the research agenda of vocabulary learning. Keeping that in mind, this research is aimed to investigate university student’s emotional experiences of learning vocabulary through English learning accounts on Instagram. The respondent of this research was a university student from non-English department in sixth semester who studying in one of universities in Lampung province, Indonesia. In order to occupy this research goal, a narrative inquiry is involved to excavate the experiences of a multifaceted kinds of positive and negative emotions. A semi structure interview through Zoom application is employed to collect the data of this research. All of data are analysed by using Braun and Clarke’s thematic analysis theory with several steps comprised of reading, coding, theming and interpreting. The result of this research reveals that emotions like happiness, satisfaction, inclination, and security may influence his willingness, feeling, motivation, and learning strategy. Meanwhile, emotions of unhappiness, insecurity and dissatisfaction are signified as the source of the obstacles in learning vocabulary through these accounts. As a matter of this fact, it can be said that emotions play a significant role during the process of learning vocabulary since there is no language learning process without the existence of emotions. Keywords: Emotions, English learning accounts, Vocabulary learning